The Role of Fluorine Substitution in the Structure-Activity Relationships (SAR) of Classical Cannabinoids. - Crocker, Peter J. (2007)
A facile synthesis of 1-fluoro-1-deoxy-Δ8-THC analogs with side-chains seven carbons in length, in the alkane/ene/yne-series (6, 5 and 4), was achieved from 1-fluoro-3,5-dimethoxybenzene (1). In vitro studies show that substitution by a fluorine has a significant detrimental effect on CB1 binding which is supported by in vivo testing. The implications of these results on the SAR of classical cannabinoids is discussed.